马来西亚的粤剧发展——以蔡艳香为案例研究 (The Development Of Malaysian Cantonese Opera: A Case Study Of Choy Yim Heong) - Loke, Mei Thing (2019)
Chinese opera is one of the oldest ancient operas in the world, and it is also a type of opera that has spread widely in the world. Cantonese opera is China's first opera to go to the world. With the footprints of Guangdong immigrants coming to Malaysia, it has taken roots and has a history of more than 100 years. This thesis discusses the beginning of Cantonese opera in Malaysia, and its ups and downs in every decade. It further discusses the life of the opera artist, Choy Yim Heong in the limelight for more than 70 years. This thesis adopts macroscopic and microscopic two-way progress, diachronic and synchronic, and outlines the evolution of Cantonese opera in the context of China’s immigrant society. It also highlights Choy Yim Heong’s contributions to the inheritance of traditional Cantonese opera art culture. This thesis is on the Cantonese opera master Choy Yim Heong as the research sample, exploring her long career on stage and to have a peek into the development of our Malaysian Cantonese opera from another perspective. In addition, the last section of this thesis also discuss on how Cantonese opera has become the strongest opera among others in Malaysia and attempts to analyse the social function transformation of Cantonese opera in Malaysia in around 100 years. From this, a prediction is made into the future of Cantonese opera in Malaysia. The writer tries to piece together the historical gaps in Cantonese opera through the use of oral information and printed references. iv The early Cantonese opera in Malaysia was dominated by foreign theatre troupes. These artists with high artistic accomplishments left a precious traditional performance technique for the opera in our country to grow and to nurture opera actors which made the country the ‘second hometown of Cantonese opera’. The first local amateur Cantonese opera club was first established around the 1920s to enrich the entertainment life of the members, promoted Cantonese art culture and charity performances. With the withdrawal of the foreigne troupe from Malaya in the late 1920s, the local Chinese organised their own professional Cantonese opera troupes for commercial and religious performances. Malaysian Cantonese opera was once reknown and had successfully produced the famous opera artist, Choy Yim Heong. Choy Yim Heong began her artistic career during the Japanese Occupation in Malaya and gained fame during Malayan Emergency Period. In the 1960s, she was already well-known actor in South-East Asia and Hong Kong. In the 1970s, Choy Yim Heong changed her performance roles into older characters and clowns to give way to the younger actors. Since then, she has become a master in Cantonese opera. During the period, she served as the chairman of the Pat Woh Association Malaysia for 22 years. She has contributed tremendously in the development of Cantonese opera in the country and at the beginning of the 21st century, she successfully reignited the cultural tradition of Cantonese opera in Guangdong and Hong Kong. In 2018, Choy Yim Heong was invited again to chair the Pat Woh Association Malaysia. Cantonese opera is the strongest opera among all traditional Chinese operas in Malaysia. Based on common moral concepts and cultural opinions, members of the Chinese communities were able to break through the barriers of the dialect group and v promote Cantonese opera to become one of the cultural symbols of the Chinese community. The main functions of Cantonese opera had been to entertain the mass and for commercial purposes since its inception and during the glory days of the 1960s and 1970s. In mid 1950s, Cantonese opera started as religious performances and since then this kind of performances had begun to replace the entertainment and commercial performances. In the 1980s, Cantonese opera in the country faced a decline and could only be extended to religious ritual activities. In order to revive the performance value of Cantonese opera to the masses, we must reconsider the functions and positions of Cantonese opera in today’s society. Bring Cantonese opera into learning institutions and create a Cantonese opera Cultural and Creative Industry to ensure its survival. This arduous task can only fall back on Chinese society itself.